Modeling Reactive Ammonia Uptake by Secondary Organic Aerosol in a Changing Climate: A WRF-CMAQ Evaluation - Zhu, Shupeng; Wu, Kai; Nizkorodov, Sergey A.; Dabdub, Donald (Frontiers in Environmental Science, 2022)
In addition to the well-constrained inorganic acid-base chemistry of ammonia resulting in fine particulate matter (PM2.5) formation, ammonia also reacts with certain organic compounds in secondary organic aerosol (SOA) to produce less basic nitrogen-containing organic compounds. In this study, the potential meteorology and air quality impacts of the heterogeneous uptake of NH3 by SOA are investigated using the WRF-CMAQ two-way coupled model, which calculates the two-way radiative forcing feedback caused by aerosol between meteorology and chemistry in a single simulation. Simulations with and without the NH3-SOA uptake are performed over the contiguous US for July 2014 and July 2050 under the RCP 8.5 IPCC scenario to study the potential impact of climate change. A comparison with multiple observation network data shows that the NH3-SOA uptake improves the model performance for PM2.5 prediction (bias reduced from -22% to -17%), especially the underestimation of organic carbon over the Southeastern US (bias reduced from -17% to -7%). Secondly, the addition of the NH3-SOA chemistry significantly impacts the concentration of NH3 and NH4+, thus affecting the modeled particle acidity. Including the NH3-SOA uptake also impacts the meteorological conditions through the WRF-CMAQ two-way feedback. Moreover, the impact on meteorological conditions results in different windspeed or dispersion conditions, thus affecting air quality predictions. Finally, simulations including the NH3-SOA uptake under the warmer climate conditions of 2050 show a smaller impact on air quality predictions than it does under current climate conditions. This study confirms the importance and necessity of including NH3-SOA chemistry in air quality predictions.